Fat kids. Issue 2 (2nd July 2016) - Boero, Natalie; Thomas, Pattie
ABSTRACT: The authors introduce the special issue on fat kids by making the argument that children and childhood need to be more central to the interdisciplinary project of fat studies. The authors discuss existing work on fatness and kids within fat studies and related disciplines. They argue that these works, though important in their documentation of the experiences of fat kids, do not do enough to place fat kids and childhood at the center of theoretical and empirical work within Fat Studies. They outline the articles presented in this special issue and conclude with a discussion of how fat studies and childhood studies might further place fat kids, childhood, and parenting at the center of their theoretical, empirical, and political projects.